Pragmatic meaning in Matthew 13 - du Plessis, J. (Neotestamentica, 1987)
Matthew 13:1-23 is analysed with the help of the pragmatic principles formulated by G.N.Leech. The analysis is performed within W.Schmid's scheme of narrative roles. The intended effect (pragmatic force) of the discourse is the strengthening of the interpersonal relationship between Jesus and his disciples. The stress is on Jesus as the dominant partner in this relationship. The disciples (and the readers) are urged to adhere in a dependent attitude to Jesus. In this way they become part of the future success of the kingdom. The remark about purpose of the parables can only be understood against this background. They are a foil used by Jesus to illuminate the relationship between himself and his disciples.